The Zero Moment of Truth in Mass Customization - Aichner, Thomas (International Journal of Industrial Engineering and Management, 2012)
Mass Customization (MC) companies can not sell their products in traditional stores. This implies thatcustomers take their purchase decision on a different level, the Zero Moment of Truth (ZMOT). Companies need to know when and where this happens, how the decision making process of their potential customers works and how it is influenced by product-related concepts such as purchase intention, product knowledge and product involvement. This paper gives an answer to these questions and provides implications for marketing managers of MC companies. Finally, a definition of the ZMOT in MC is formulated. Article history: Received (08 November 2012); Revised (25 November 2012); Accepted (02 December 2012)